Development of research competencies through artificial intelligence. An innovative approach - Cárdenas-Velasco, Kléver (2025)
The article presents the topic on the Development of research competencies through artificial intelligence. An innovative approach. It responds to the constructivist paradigm that focuses on active learning based on the context of experiences and cognetivism, proposes knowledge networks with technology management for the construction of learning. Ideas are described to help solve the current problem, since teachers and students do not have sufficient knowledge of Artificial Intelligence (AI) and its relationship with research competencies. The objective is to propose the optimization of the educational process with the incorporation of AI and the development of research skills in students. It is based on updated contents on the two main topics, with emphasis on their ethical dimension. The analytical-synthetic method was used; documentary analysis and bibliographic review with specialized scientific information that supports the work and projects its results to other possible studies. It is concluded that there is a need to incorporate AI progressively in educational institutions, in which the necessary virtual support should be installed so that research competences are applied in the learning process and can be efficiently managed by teachers and gradually by students. It is an indispensable requirement to achieve a qualitative improvement in the educational processes in order to leave aside verbalism and give way to the formation of cooperative groups in which students raise their concerns, seek alternative solutions and find their own answers.